Expectations and Perceptions of Service Quality in Old and New Generation Banks-A Study of Select Banks in the South Canara Regions - Joshua, A J; Koshi, Moli. P. (Indian Journal of Marketing, 2005)
Recognition of service quality as a competitive weapon is relatively a recent phenomenon in the Indian Banking sector. Prior to the liberalization era the banking sector in India was operating in a protected environment and was dominated by nationalized banks. Banks at that time did not feel the need to pay attention to service quality issues and they assigned very low priority to identification and satisfaction of customer needs..